Genetic predisposition to Alzheimer's disease - Hálová, Alice; Ambrozová, Laura; Ambroz, Petr; Zatloukalová, Anna; Machaczka, Ondřej; Janoutová, Jana; Janout, Vladimír (Profese Online, 2020)
Background: Alzheimer's disease is the most common neurodegenerative disease, which is caused by a number of factors - one of them is genetic predisposition Whole-genome association studies make it possible to find candidate genes whose changes could contribute to the development of this disease. Aim: This literature review summarizes the findings of whole-genome association studies aimed at determining the genetic predisposition to late-onset Alzheimer's disease. Its aim is to compile an overview of candidate genes associated with this disease for future research. Methods: The work is processed in the form of literary research. It describes important genes that are associated with late-onset Alzheimer's disease. Results: Based on previous experience, the genes APOE, TOMM40, CD36, CLU, CHAT, IDE and TNK1 were selected, which are the most suitable candidates for future targeted genetic testing in the Czech population. Conclusions: This work presented a list of genes associated with late-onset Alzheimer's disease. Future research in this area can make a significant contribution to the prediction and subsequent prevention of this serious disease.
Keywords: Alzheimer's disease; genes; APOE; TOMM40; CD36; CLU; CHAT; IDE; TNK1